Examining the Formalin Fixation Method for Maintaining High RNA Quality in Surgical Lung Specimens - Takashi Teishikata; Manabu Itoh; Yusuke Okamoto; Naofumi Miyahara; Chiho Nakashima; Koichiro Takahashi; Masafumi Hiratsuka; Keita Kai; Keiji Kamohara (Thoracic Cancer)
ABSTRACT Background Multiplex genetic testing is recommended when treating nonsmall cell lung cancer. A certain percentage of test failures in RNA assays owing to poor surgical specimen quality have been documented, and fixation failure is a possible cause. At our institution, sheet‐like fixation is performed to reduce fixation time. This study aimed to compare the quality of RNA from resected lung cancer specimens following different fixation methods. Methods Sheet‐like fixation specimens (n = 15), conventional fixation specimens of the same resected lungs (n = 15), and other lung cancer specimens collected for conventional fixation and subjected to multiplex gene‐panel testing (n = 22) were retrospectively examined. RNA was extracted from each specimen. RNA quality and quantity were compared, and the success rate of multiplex gene‐panel testing was determined. Results The DV200 value was significantly higher in RNA extracted from sheet‐like fixation samples (median 47.5%, interquartile range [IQR]:40.3–51.5) compared with RNA extracted from conventionally fixed samples or conventionally fixed samples of other patient specimens (median 21%, IQR:5.3–29.8 and median 16.3%, IQR:9.5–27.1, respectively). No significant difference was observed in nucleic acid concentration. The multiplex genetic analysis success rate was 95% with conventional methods (one failure); however, it was 100% with the sheet‐like fixation method. Conclusion Sheet‐like fixation preserved RNA extracted from lung cancer specimens, resulting in lesser degradation than with conventional fixation.